Charcot Neuroarthropathy of the Foot and Ankle. (18th April 2018) - Dodd, Andrew; Daniels, Timothy R.
Abstract : Charcot neuroarthropathy (CN) is a systemic disease that generates pathological changes in the musculoskeletal system, causing fractures, dislocations, and deformities involving the foot and ankle. A common underlying cause of CN is diabetes mellitus; a substantial risk of ulceration and deep infection contributes to a 15% rate of major amputation (i.e., at the level of the ankle or higher). The goal of both nonsurgical and surgical treatment of CN is to obtain a stable, plantigrade foot free from ulcerations; an equally important goal is to manage the patient's diabetes and obesity. The primary indications for surgery are recurrent ulceration, substantial deformity, deep infection, and pain; common complications include nonunion, wound breakdown, and infection. The principles of thorough joint preparation, deformity correction, and minimizing soft-tissue trauma are essential when arthrodesis is performed for CN, which requires more robust (internal and/or external) fixation and prolonged off-loading.